Analisis Kombinatorik Dalam Menentukan Keamanan dan Kompleksitas Password dengan Penerapan Teori Kombinatorik - Arnah Ritonga; Bobby Putra Delon Togatorop; Herdita Br Ginting; Klara Manila Laoli; Monica Tri Yuni Sinaga; Rina Intan Amelia; Widya kartini pangaribuan (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
Password security is a crucial aspect of digital authentication systems; however, many users still rely on weak and easily guessable passwords, increasing their vulnerability to cyber threats such as brute force and dictionary attacks. This study aims to evaluate password strength based on length and character complexity using a combinatorial theory approach. Through simulations, this research calculates the number of possible character combinations for various password lengths and character types, including lowercase letters, uppercase letters, numbers, and symbols. Additionally, the study estimates the time required to crack different types of passwords using brute force techniques and compares the results with real-world password breach data. The simulation results reveal that passwords composed solely of lowercase letters and fewer than eight characters in length can be cracked within seconds. In contrast, passwords that include a combination of uppercase and lowercase letters, numbers, and symbols with a minimum length of 12 characters would require more than one million years to be deciphered through brute force methods. These findings emphasize that increasing both the length and complexity of passwords significantly enhances security strength. Therefore, users are strongly encouraged to create passwords that are at least 12 characters long and include a diverse mix of character types. Furthermore, implementing Multi-Factor Authentication (MFA) and using password managers are highly recommended strategies to improve account protection. By adopting these practices, the risk of data breaches due to compromised passwords can be substantially reduced, contributing to stronger and more resilient digital security environments.